2016
DOI: 10.1007/s10567-016-0212-3
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Behaviour Therapy for Children and Adolescents: Can Attachment Theory Contribute to Its Efficacy?

Abstract: Meta-analyses consistently demonstrate that cognitive behaviour therapy (CBT) provides effective evidence-based treatment for children and adolescents with emotional and behaviour problems. Also consistent across meta-analyses is the observation that CBT treatment effects are often medium in size. This observation has instigated a search for factors that could help explain the limited treatment effects and that could be focused upon to enhance CBT treatment outcomes. The current qualitative review focuses on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 134 publications
2
58
0
4
Order By: Relevance
“…These findings also contribute to attachment research: the finding that an increased attentional focus on the mother is maladaptive when children remain caught in thoughts about their mother, seems a middle childhood equivalent to Cassidy and Berlin's (1994) and Main's (2000) observation of an increased, inflexible focus on the mother in some insecurely attached infants. However, attachment theory, research, and related interventions have been limited by concerns about precise definition and measurement of these constructs (Bosmans, 2016;Rutter, 2014;Thompson, 2008). The current line of research could help to define more concretely which attachment-related cognitive processes might be involved in the prevalence of psychopathology and how.…”
Section: Running Head: Increased Focus On Mother and Depressive Symptomsmentioning
confidence: 99%
“…These findings also contribute to attachment research: the finding that an increased attentional focus on the mother is maladaptive when children remain caught in thoughts about their mother, seems a middle childhood equivalent to Cassidy and Berlin's (1994) and Main's (2000) observation of an increased, inflexible focus on the mother in some insecurely attached infants. However, attachment theory, research, and related interventions have been limited by concerns about precise definition and measurement of these constructs (Bosmans, 2016;Rutter, 2014;Thompson, 2008). The current line of research could help to define more concretely which attachment-related cognitive processes might be involved in the prevalence of psychopathology and how.…”
Section: Running Head: Increased Focus On Mother and Depressive Symptomsmentioning
confidence: 99%
“…Beyond being a new assessment tool, by providing an alternative perspective to understand the cognitive underpinnings of the attachment representations, ASA has become an intriguing method not only for attachment but also for cognitive therapy literature. It has been discussed that conceptualizing and assessing attachment representations as cognitive secure base scripts may offer alternative answers to some questions that are still be sought in cognitive therapies (Bosmans, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…İlk olarak İÇM'lerin yapısına dikkat çeken Bretherton (1990); bu modellerin dil gelişiminden önceki dönemde yapılandığına dikkat çekerek, bağlanma temsilinin semantik bilgiden ziyade, duygu düzenlemeye (stres yönetimine) yönelik işlemsel bilgi içeren senaryolardan oluştuğunu öne sürmüştür. Waters ve Rodrigues-Doolabh (2001) Deneyim ve bilişsel gelişimle çocuğun zihninde neden-sonuç zinciri olarak yapılandığı belirtilen bu temsiller, Waters ve Waters (2006) (Bosmans, 2016). Çoğu bilişsel terapi yaklaşımı, erken dönem bağlanma ilişkisinin en derindeki inançları yapılandırdığını ifade etmektedir (Beck, 1995;Safran, 1990;Young, 1999 (Bosmans, 2016).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Short admission was thought to be feasible, since research showed most health gains to occur during the first weeks [16,17,18]. IHT principles are primarily based on solution-focused therapy [19] and attachment based family therapy (Bosmans, 2016), although individual interventions (e.g., medication, cognitive behaviour therapy) can be provided as well. IHT strongly focuses on improvement of the relationship between patient and caregivers, reintegration into school, work and hobby, reducing self-harming behaviour and increasing the adolescent's motivation for therapy.…”
Section: Introductionmentioning
confidence: 99%